2023
DOI: 10.1155/2023/7773609
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Delivery of H2 through Ammonia Borane-Loaded Hollow Polydopamine for Intervertebral Disc Degeneration Therapy

Abstract: An imbalance in oxidative and inflammatory regulation is the main contributor to intervertebral disc degeneration (IDD). Hydrogen (H2) therapy is a promising antioxidation and anti-inflammatory approach. However, the key to the treatment is how to maintain the long-term effective H2 concentration in the intervertebral disc (IVD). Therefore, we developed a pH-responsive delivery of H2 through ammonia borane-loaded hollow polydopamine (AB@HPDA) for IDD therapy, which has sufficient capacity to control long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…This specially designed complex, called AB@HPDA, is characterized by a large surface area, high biocompatibility, and permeability. 112 The complex is incorporated into the nanoparticles and can be injected at degenerated positions. In vivo experiments showed that this injectable nanoparticle significantly reduced tissue oxidative damage by the pH-responsive delivery of H 2 and restored normal physiological functions.…”
Section: Internal Stimuli-responsive Delivery Systems For Ivddmentioning
confidence: 99%
See 1 more Smart Citation
“…This specially designed complex, called AB@HPDA, is characterized by a large surface area, high biocompatibility, and permeability. 112 The complex is incorporated into the nanoparticles and can be injected at degenerated positions. In vivo experiments showed that this injectable nanoparticle significantly reduced tissue oxidative damage by the pH-responsive delivery of H 2 and restored normal physiological functions.…”
Section: Internal Stimuli-responsive Delivery Systems For Ivddmentioning
confidence: 99%
“…In vivo experiments showed that this injectable nanoparticle significantly reduced tissue oxidative damage by the pH-responsive delivery of H 2 and restored normal physiological functions. 112 …”
Section: Internal Stimuli-responsive Delivery Systems For Ivddmentioning
confidence: 99%